Keratocystic odontogenic tumor of the right mandibular condyle: A rare case - Kamala Rawson; Basavaraj N Kallalli; Swaroop Telkar; Mohan Raju Penumatcha (Wolters Kluwer Medknow Publications, 2014)
Odontogenic keratocyst (OKC) was first described by Hans Philipsen in 1956. The World Health Organization (WHO) has designated OKC as a Keratocystic Odontogenic Tumor (KCOT). KCOT is defined as 'a benign uni- or multicystic, intraosseous tumor of odontogenic origin, with a characteristic lining of parakeratinized stratified squamous epithelium, with a potential for aggressive, infiltrative behavior'. Radiographically, most OKCs are unilocular, presenting a well-defined peripheral rim and a central cavity having satellite cysts. It is characterized by a thin fibrous capsule and a lining of keratinized stratified squamous epithelium, which is typically corrugated, usually about 6 to 10 cells in thickness, and generally without rete pegs. The present case report describes an unusual case of KCOT with minimal clinical presentation indicative of a tumor highlighting the potential difficulties in determining the diagnosis.